Ultrasound-MR fusion imaging combined with intraductal cooling via PTCD during microwave ablation of perihilar liver tumors: a retrospective pilot study - Jiangyu Guo; Shuang Liang; Huahui Liu; Liping Luo; Shanshan Wu; Sainan Guan; Ying Liu; Yongyan He; Erjiao Xu; Ronghua Yan (International Journal of Hyperthermia)
Purpose To explore the feasibility and safety of a microwave ablation (MWA) strategy involving intraductal chilled saline perfusion (ICSP) via percutaneous transhepatic cholangial drainage (PTCD) combined with ultrasound-magnetic resonance (US-MR) fusion imaging for liver tumors proximal to the hilar bile ducts (HBDs).Methods Patients with liver tumors proximal to the HBDs (≤5 mm) who underwent MWA at our hospital between June 2020 and April 2023 were retrospectively analyzed. The strategy of US-MR fusion imaging combined with PTCD-ICSP was used to assist the MWA procedures. The technical success, technique efficacy, local tumor progression, intrahepatic distant recurrence and complications were recorded and analyzed.Results In total, 12 patients with 12 liver tumors were retrospectively enrolled in this study. US-MR fusion imaging was utilized in all patients, and PTCD-ICSP assistance was successfully used for 4 nodules abutting HBDs (0 mm). The rates of technical success, technique efficacy, local tumor progression and intrahepatic distant recurrence were 91.7%, 83.3%, 0% and 8.3%, respectively. The major complication of biliary infection occurred in only one patient who had previously undergone left hemihepatectomy and bile-intestinal anastomosis.Conclusions MWA for liver tumors proximal to HBDs assisted by US-MR fusion imaging combined with PTCD-ICSP was feasible and safe. This strategy made MWA of liver tumors abutting HBDs possible.